PERBEDAAN PENDIDIKAN AGAMA DI NEGARA JEPANG DAN NEGARA INDONESIA - Deding Ishak (Jurnal Kelola: Jurnal Ilmu Sosial, 2021)
Each country has differences in religious and educational policies. This policy difference also occurs in Indonesia and Japan. This study then analyzes the differences that exist in religious education in Japan and Indonesia in various aspects. This research was conducted using a qualitative approach. The data comes from the results of previous studies and research. The results of this study indicate that there are differences in the implementation carried out by Japan and Indonesia. Japan does not really care about religious education, while Indonesia fully supports religious education in their country. This difference is not only caused by the character of the people, but also the ideological differences of different countries. However, both countries have an important role for religious education in their respective countries.